Inversão de relevo nos maciços de Portalegre e Martins - NE do Brasil: controle morfotectônico e erosão diferencial como proposta de evolução geomorfológica - Coelho, Gerliane Kelly de Sousa (2022)
Relief inversion corresponds to the elevation of a given surface, such as old agrational areas to high elevations, either by the influence of tectonics or/and by the action of differential erosion. The presence of sedimentary rocks preserved on high structures can be characterized as important indicators of relief inversion processes, since they were part of an old depositional base level. Expressive remains of sandstone rock, known as the Serra do Martins Formation, are found in the Northeastern region of Brazil, in the Martins and Portalegre massifs. The sedimentary unit, dating from the Cenozoic, has continental origin and is located between altitudes that vary from 650 to 700m in altitude, functioning as a kind of protective mantle, preserving the geomorphology of the current relief. The FSM depositional systems are already well known, but their chronology is still the result of discussions that support different models of geomorphological evolution. The present work seeks to analyze the different aspects of geological and geomorphological evolution, as it contributes to the alteration of base levels, of erosion leading to dissection. For this, it was necessary to correlate cartographic, altimetric and structural data with bibliographic data and fieldwork. The processes of topographic inversion and dissection and relief orientation were conditioned from two main elements, the control exerted by the differential erosion of the basement, emphasizing the double resistance factor measured by the FSM sandstones and the granites of the Itaporanga and Poço da Cruz, and the syn and post-rift tectonics, considering the influence of the Portalegre Shear Zone, in addition to working on the influence of the Potiguar basin and the Pereiro massif in the topographic inversion process. Through fieldwork, the erosive behavior of the slopes was analyzed. Those covered by FSM sandstones had escapes with concave characteristics, in a process of lateral retraction (backwearing), due to the protective action of the lateritic duricrust. The escarpments with exposed granite have a convex tendency. There was marked dissection in the southern part of the Martins massif, due to the exposure of the alteration front, leaving the crystalline summit more fragile to the action of erosive/weathering processes. Thus, the results of this research are presented as a contribution to the understanding of the processes of geomorphological evolution of the Portalegre and Martins massifs.